2016
DOI: 10.3389/fpsyg.2016.01665
|View full text |Cite
|
Sign up to set email alerts
|

Is Mixed Practice More Effective than Physical Practice Alone for the Acquisition of Non-dominant Side Kicking Performance?

Abstract: Perceiving and executing unfamiliar movements, such as left handed/footed movement skills in sports, places additional demands on the perceptual-cognitive system of players that may increase errors. The video self-modeling (VSM) method may provide an accessible solution to this issue, therefore the purpose of this study was to investigate the effect of the VSM method on the improvement of a non-preferred side kicking task. N = 28 participants engaged in one of three conditions; Mirror reversed/ physical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Carey et al, 2001;Petro & Szabo, 2016;Stöckel & Weigelt, 2012), the efficacy of mirror visual feedback, and the availability of mirrored video self-modelling, the method has received little VOLUME 13 | ISSUE 3 | 2018 | 623 attention. We are aware of three published papers testing the method of which one is ours (Petro & Bárdos, 2014;Steel, Adams, Coulson, Canning, & Hawtin, 2013;Steel & Ellem, 2016). These studies, in spite of different methodology, have revealed promising results that merit further investigations.…”
Section: Introductionmentioning
confidence: 97%
“…Carey et al, 2001;Petro & Szabo, 2016;Stöckel & Weigelt, 2012), the efficacy of mirror visual feedback, and the availability of mirrored video self-modelling, the method has received little VOLUME 13 | ISSUE 3 | 2018 | 623 attention. We are aware of three published papers testing the method of which one is ours (Petro & Bárdos, 2014;Steel, Adams, Coulson, Canning, & Hawtin, 2013;Steel & Ellem, 2016). These studies, in spite of different methodology, have revealed promising results that merit further investigations.…”
Section: Introductionmentioning
confidence: 97%